2008
DOI: 10.1002/bem.20419
|View full text |Cite
|
Sign up to set email alerts
|

Effects of weak mobile Phone—Electromagnetic fields (GSM, UMTS) on well‐being and resting EEG

Abstract: Modern mobile phones emit electromagnetic fields (EMFs) ranging from 900 to 2000 MHz which are suggested to have an influence on well-being, attention and neurological parameters in mobile phone users. To date most studies have investigated Global System for Mobile Communications (GSM)-EMF and only very few studies were concerned with Universal Mobile Telecommunications System (UMTS)-EMF. Consequently, we tested the effects of both types of EMF, 1950 MHz UMTS (SAR 0.1 and 1 W/kg) and pulsed 900 MHz GSM (1 W/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 23 publications
4
37
0
Order By: Relevance
“…It was demonstrated that the results (and conclusions) strongly depend on the method of analysis. Analysed in the traditional fashion, that is, not controlling for the nested structure of the data, no significant differences could be demonstrated (see table 2), a finding which is in accordance with several other studies (97,(101)(102)(103)(104). However, when the data were analysed with an appropriate multilevel statistical model, 'radiation' proved to be a significant predictor of the alpha, slow beta, fast beta, and gamma frequency bands over almost all brain regions ( Figure.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It was demonstrated that the results (and conclusions) strongly depend on the method of analysis. Analysed in the traditional fashion, that is, not controlling for the nested structure of the data, no significant differences could be demonstrated (see table 2), a finding which is in accordance with several other studies (97,(101)(102)(103)(104). However, when the data were analysed with an appropriate multilevel statistical model, 'radiation' proved to be a significant predictor of the alpha, slow beta, fast beta, and gamma frequency bands over almost all brain regions ( Figure.…”
Section: Discussionsupporting
confidence: 87%
“…First, in most studies a control session was included on a separate day (43,44,94,95,97). It is known, however, that resting EEGs can differ across days, even without any intervention (98).…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of various physiological effects and performance measures in the study of biological effects of electromagnetic fields are observed. [6] The effects investigated in Global System for Mobile Communications (GSM)-EMF and Universal Mobile Telecommunications System (UMTS)-EMF are tested. Significant changes in the measured parameters are not produced when compared to sham exposure which is the control group used to simulate the environmental conditions of exposed samples in the absence of exposure.…”
Section: Literature Surveymentioning
confidence: 99%
“…Mobile phones are low-powered radio devices that transmit and receive radio frequency radiation at 900-2000 MHz [7,8]. They are mainly placed in the front or side pockets of clothes or hung on a belt and held close …”
Section: Introductionmentioning
confidence: 99%